317 Prevalence of Thoracic Aneurysms or Dilatations in Patients With the Intracranial Aneurysms. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Laukka, Dan; Pan, Emily; Fordell, Terhi; Alpay, Kemal; Rahi, Melissa; Hirvonen, Jussi; Rinne, Jaakko; Gunn, Jarmo
Abstract: INTRODUCTION: Aortic aneurysms and intracranial aneurysms (IA) shares similar comorbidities and genetic risk factors. Patients with thoracic aortic aneurysms have higher prevalence of IAs compared to general population. However, larger scale studies evaluating the entire thoracic aorta in the patients with IA and in relation to fusiform IAs are not available. METHODS: We reviewed retrospectively records for 1777 patients diagnosed with ruptured or unruptured IAs at our institution between 2006 and 2016. From these patients we included 519 patients with an available contrast-enhanced computed tomography angiography, unenhanced computed tomography, magnetic resonance image/angiography, or catheter arteriography with sufficient coverage of the chest area to reliably evaluate thoracic aortic dimensions. Thoracic aortic dimensions were compared to reference values of general population. RESULTS: From 519 patients, 94.6% (n = 491) had saccular and 5.4% (n = 28) fusiform IA, 41.6% (N = 216) had ruptured and 56.4% unruptured IA. In patients with saccular IA, total prevalence of thoracic aortic dilatations and aneurysms was 17% and 6% and in patients with fusiform IA prevalence was 29% and 18%. Aortic arch was the most common location for thoracic aortic dilation (prevalence 64%) in patients with saccular IA and ascending aorta in patients with fusiform aneurysm. Rheumatoid disease (odds ratio [OR] 3.00, P  = .008) and alcohol abuse (OR 3.69, P  = .007) were significant risk factors for aortic dilatation in multivariate analysis. CONCLUSION: The prevalence of thoracic aortic aneurysms and dilatations is higher in patients with intracranial saccular aneurysms and especially in patients with fusiform aneurysms compared to reports from the general population. Patients with saccular IAs and a history of rheumatoid disease and/or excessive alcohol consumption and patients with fusiform IA have a very high risk for thoracic aortic aneurysms and dilatations and could be considered for thoracic aortic aneurysm screening.